2017
DOI: 10.1097/fpc.0000000000000252
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of atorvastatin pharmacokinetics and the identification of the effect of a BCRP polymorphism in the Japanese population

Abstract: Aim(s): Ethnicity has a modulating role in atorvastatin pharmacokinetics, with Asian subjects reported to have higher exposure compared to Caucasians. Therefore, it is difficult to safely extrapolate atorvastatin pharmacokinetic data and models across ethnic groups. This work aims to develop a population pharmacokinetic model for atorvastatin and its pharmacologically active metabolites specifically for the Japanese population. Subsequently it is aimed to identify genetic polymorphisms affecting atorvastatin p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 52 publications
(69 reference statements)
0
6
1
Order By: Relevance
“…[40][41][42][43][44] Some population PK (PopPK) studies have been published but with strict, rich sampling and/or in a limited number of (healthy) individuals without considering genetic polymorphisms and, thus, are not likely to reflect the constraints of real-life clinical settings. 29,[45][46][47][48] In this context, with the support of rich datasets from former studies, 49,50 our study aimed at constructing a PopPK model with data prospectively collected in a cohort of ambulatory patients sparsely sampled and including relevant pharmacogenetic information. Next, we derived the apparent clearance (CL/F) of the drug in each individual and related it with indicators of statin-related muscle toxicity and cholesterol-lowering response.…”
Section: How Might This Change Clinical Pharmacology or Translational...mentioning
confidence: 99%
“…[40][41][42][43][44] Some population PK (PopPK) studies have been published but with strict, rich sampling and/or in a limited number of (healthy) individuals without considering genetic polymorphisms and, thus, are not likely to reflect the constraints of real-life clinical settings. 29,[45][46][47][48] In this context, with the support of rich datasets from former studies, 49,50 our study aimed at constructing a PopPK model with data prospectively collected in a cohort of ambulatory patients sparsely sampled and including relevant pharmacogenetic information. Next, we derived the apparent clearance (CL/F) of the drug in each individual and related it with indicators of statin-related muscle toxicity and cholesterol-lowering response.…”
Section: How Might This Change Clinical Pharmacology or Translational...mentioning
confidence: 99%
“…The Keskitalo group ( 39 ) found that carriers of the c. 421AA genotype had a 72 % larger mean atorvastatin AUC than those with the c. 421CC genotype. Another study ( 91 ) in a Japanese population revealed that patients carrying the rs2622604 ABCG2 allele variant had a 55 % increase in oral atorvastatin bioavailability vs non-carriers.…”
Section: Discussion and Review Of Drug-drug-gene Interactionsmentioning
confidence: 99%
“…The present study also identified large between-subject variability in atorvastatin clearance and central volume of distribution. Although non-compartmental analyses showed an effect of age on atorvastatin disposition [ 10 , 11 ], the majority of previously published population PK analyses did not report any significant influence [ 13 , 14 , 16 ], while one of the studies found an effect in men only [ 12 ]. In our study, this association did not reach statistical significance, although visual inspection of the plots evaluating the effect of age on atorvastatin clearance suggested a slight decrease in clearance for PLWH older than 60 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…One non-compartmental PK study showed an effect of sex (11% decrease in area under the curve [AUC] in women) on atorvastatin disposition [11]. Moreover, population PK studies indicate a body weight-related decrease in atorvastatin clearance [13], an influence of liver enzymes (aspartate aminotransferase [AST] and lactate dehydrogenase) on atorvastatin disposition [14,15], and an effect of polymorphisms in the intestinal breast cancer resistance protein (BCRP) on atorvastatin bioavailability [16]. However, to our knowledge, no study investigated the effect of ARVs on atorvastatin disposition in a real-life setting.…”
Section: Introductionmentioning
confidence: 99%